Perforation of a Retrocecal Appendix Resulting in Retroperitoneal Air: A Case Report. (11th February 2013) - Litkouhi, Behrang; Huang, Alicia S.; Lundy, David J.; Solis, Maria
Abstract : There have been several case reports documenting acute appendicitis complicated by perforation presenting with retroperitoneal abscess formation. To date, there are no case reports of acute appendicitis in which the only sign for retroperitoneal perforation is the presence of retroperitoneal air as detected by computed tomography (CT). In the case presented, an 18-year-old male presented to the emergency department with clinical symptoms of acute appendicitis. CT exam demonstrated an inflamed appendix with multiple collections of air in the retroperitoneum, without abscess. Laparotomy revealed perforation of a retrocecal appendix into the retroperitoneum.